Identification of novel Theileria genotypes from Grant's gazelle. Issue 2 (August 2015) - Hooge, Janis; Howe, Laryssa; Ezenwa, Vanessa O.
Highlights: One hundred percent of 65 Grant's gazelle blood samples were PCR-positive for Thelieria/Babesia . Sequencing of PCR amplicons revealed widespread Theileria co-infections. Isolates from singly infected animals fell into two Theileria subgroups. One of these subgroups clustered with Theileria ovis isolates from livestock. The gazelle Theileria lineages represent novel genotypes. Graphical Abstract: Abstract: Blood samples collected from Grant's gazelles ( Nanger granti ) in Kenya were screened for hemoparasites using a combination of microscopic and molecular techniques. All 69 blood smears examined by microscopy were positive for hemoparasites. In addition, Theileria/Babesia DNA was detected in all 65 samples screened by PCR for a ~450-base pair fragment of the V4 hypervariable region of the 18S rRNA gene. Sequencing and BLAST analysis of a subset of PCR amplicons revealed widespread co-infection (25/39) and the existence of two distinct Grant's gazelle Theileria subgroups. One group of 11 isolates clustered as a subgroup with previously identified Theileria ovis isolates from small ruminants from Europe, Asia and Africa; another group of 3 isolates clustered with previously identified Theileria spp. isolates from other African antelope. Based on extensive levels of sequence divergence (1.2–2%) from previously reported Theileria species within Kenya and worldwide, the Theileria isolates detected in Grant's gazelles appear to represent at least two novel Theileria genotypes.